Industrial Energy Use, Management Practices and Price Signals: The Case of Swedish Process Industry - Dahlqvist, Anna; SÃ¶derholm, Patrik (International Journal of Energy Economics and Policy, 2019)
The objectives of the paper are to: (a) derive and discuss indicators of industrial companies’ decision-making and management practices on energy use; and (b) investigate whether these practices can help explain variations in energy intensities across these companies. The data were collected through telephone interviews with 101 large industrial firms in Sweden. The indicators display a significant overall increase in firms’ awareness of energy efficiency issues over time, including the attention devoted to these issues at the top management level. Still, our econometric results show that energy prices constitute the most important determinant of inter-firm differences in energy intensities. Higher energy prices over the time-period, have induced the implementation of energy-relevant management and practices, and led to more systematic decision-making processes. Finally, firms for which so-called ‘hidden’ costs, e.g., the costs of production disruptions, are a large concern, will be more energy intense than others. Keywords: energy efficiency; industry; management practices; energy prices; Sweden. JEL Classifications: D22, L23, Q41. DOI: https://doi.org/10.32479/ijeep.7451